2012
DOI: 10.1111/j.1365-2249.2012.04611.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leishmania major clones showing different levels of virulence on infectivity, differentiation and maturation of human dendritic cells

Abstract: SummaryLeishmania parasites and dendritic cell interactions (DCs) play an essential role in initiating and directing T cell responses and influence disease evolution. These interactions may vary depending on Leishmania species and strains. To evaluate the correlation between Leishmania major (Lm) virulence and in-vitro human DC response, we compared the ability of high (HV) and low virulent (LV) Lm clones to invade, modulate cytokine production and interfere with differentiation of DCs. Clones derived from HV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…major , L . donovani [ 46 48 ] and L . amazonensis [ 49 ] promastigotes were able to significantly downregulate CD1a expression on human DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…major , L . donovani [ 46 48 ] and L . amazonensis [ 49 ] promastigotes were able to significantly downregulate CD1a expression on human DCs.…”
Section: Discussionmentioning
confidence: 99%
“…LipESP also induced significant levels of TNF-α and IL-10 in both cell populations with significantly higher cytokine-inducing capacities for LiP15 and LiAAA-ATPase. In vitro infection studies have mainly showed that in the absence of other stimuli, Leishmania parasites can trigger relatively weak or no cytokine production by DCs [ 21 , 48 , 52 54 ]. Similarly to our results, IL-12 production by infected DCs can be markedly enhanced by the addition of exogenous stimuli such as IFN-γ, IFN-γ/LPS, and CD40L [ 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Leishmania organisms on different inflammatory cells involves inhibition of dendritic cell maturation, differentiation and migration . In the presence of a high parasitic index, specifically, L. major causes further downregulation of CD1a with inhibition of Langerhans cell interleukin 12 production and resultant attenuation of the Th1 response. Due to the low interferon‐Υ, both CD80 and CD86 are downregulated on Langerhans cells causing minimal inhibition of the cytotoxic T‐lymphocyte antigen‐4 receptor on double‐negative T‐regulatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Leishmania organisms on different inflammatory cells involves inhibition of dendritic cell maturation, differentiation and migration. 33,51,52 In the presence of a high parasitic index, specifically, L. major causes further downregulation of CD1a with inhibition of Langerhans cell interleukin 12 production 40 (Fig. 6).…”
Section: Immune Response At a High Parasitic Indexmentioning
confidence: 99%
See 1 more Smart Citation